The association between Lifelines Diet Score and GDM: a case-control study - Abudari, Mohammad Othman; Alreshidi, Nahlah Fahad; Alharbi, Saud Salman; Alziyadi, Shatha Hallal; Alanazi, Mansuor A.; Kambal, Nahla; Elmansy, Fatma Mohamed; Elbqry, Mohamed Goda (Frontiers in Nutrition, 2025)
BackgroundGestational diabetes mellitus (GDM) is a common pregnancy-related complication with rising global prevalence, posing significant short-and long-term health risks to both mothers and their offspring. Various lifestyle and dietary factors have been implicated in its development. While dietary quality indices like the Lifelines Diet Score (LLDS) have shown promising associations with improved cardiometabolic outcomes, their relationship with GDM remains unclear. This study examines the relationship between the Lifelines Diet Score and the odds of gestational diabetes mellitus.MethodsThis case-control investigation was conducted at a tertiary care referral center, specifically Qassim University Hospital, with participant enrollment occurring from January 2022 to January 2025. The study cohort consisted of 150 cases and 150 matched controls. Individual food consumption was documented to compute the LLDS utilizing a semiquantitative food frequency questionnaire.ResultsA total of 300 participants (150 cases and 150 controls) were included. No significant differences were observed between groups regarding age, BMI, physical activity, smoking status, or education level. However, the case group had significantly higher gravidity (p = 0.024) and a greater family history of GDM (p = 0.041). Higher LLDS quartiles were associated with healthier nutrient profiles and favorable food group consumption, including increased intake of vegetables, fruits, legumes/nuts, and decreased intake of red/processed meats and sugar-sweetened beverages (P-trend < 0.05). Multivariable logistic regression showed a significant inverse association between LLDS and odds of GDM. Compared to the lowest quartile, participants in the highest LLDS quartile had 76% lower odds of GDM (adjusted OR: 0.23, 95% CI: 0.12–0.40; P-trend < 0.001).DiscussionOur findings indicate that greater adherence to the LLDS may be associated with reduced odds of GDM. Although the case-control design precludes causal inferences, these results highlight the potential significance of overall dietary quality in maternal metabolic health. Further prospective and intervention studies are warranted to validate these associations and elucidate the underlying mechanisms through which a high-quality diet may mitigate the odds of GDM.